Do-It-Yourself - Ledune, Eric (Belgium, 2007)
Verzio FF Submission The film is based on a real torture instruction book written by the CIA in the ‘70’s for Latin American dictatorships. Do-it-yourself explores in both a comic and a didactic manner different ways to execute without failure various successful and delightful types of torture. Torture is very often disparaged because of its association with dictatorial regimes. But what is really happening in our democracies? “Do-It-Yourself” is used within an educational dossier conceived by Amnesty International Belgique, to sensitize the public to the fact that torture has become a matter of daily life.